LITERATURE REVIEW EFFECTIVENESS THE USE OF BENGKUNG ON RECOVERY IN POSTPARTUM MOTHERS - Irmasanti Fajrin; Atik Purwandari; Debbie Christie Mogonta (Patria Artha Journal of Nursing Science, 2022)
Background : Indonesia is a country consisting of various tribes and cultures, each of which has a health tradition. some traditions have a bad effect on health but some have a positive impact on health. Bengkung is a long cloth about 10 meters long, used specifically to protect the mother's stomach after delivery. Its use begins after the 3rd to 40th day postpartum. Basically the benefit of the bengkung is to narrow the mother's movement so that her sitting position can be restrained. The purpose : of the study was to determine the effectiveness the use of bengkung on recovery in postpartum mothers based on a literature review. Method : This type of research is qualitative with literature review approach related to use of bengkung on recovery in postpartum mothers. The sources used in the electronic databases are Googlescholar, Researchgate, dan, Pubmed. The journals used in this study were published between 2015 and 2021, found 8 journals that met the inclusion criteria. Results : Analysis of the literature from eight journals found that the bengkung intervention was effective in the recovery of postpartum mothers including uterine involution, increasing milk production, reducing pain, and launching lochea expenditure and can be used as non-pharmacological therapy in the care of postpartum mothers. Conclusion, the use of jicama is effective for recovery in postpartum women. Recommendation : It is hoped that the use of Bengkung can be useful in the recovery of postpartum mothers when used with the correct technique.